Europeanisation as a Factor of National Interest Group Political-Cultural Change: The Case of Interest Groups in Slovenia. (February 2015) - Fink-Hafner, Danica; Hafner-Fink, Mitja; Novak, Meta
Based on a social constructivist framing, this article seeks to address the gap in the literature on the impact of Europeanisation on the national interest group political culture in general and in the post-communist context in particular. The impacts of Europeanisation on interest group domestic policy behaviour, in terms of national interest groups networking with their European counterparts, their contacts with EU-level decision makers, and their access to EU funds, are tested based on the panel surveys that were conducted in 1996 and 2012 of the most influential interest groups in eleven policy fields in Slovenia. Our key findings are that Europeanisation does support changes in the national interest group political culture in the direction of a more pro-active approach in influencing national policy processes. However, Europeanisation explains only a small portion of the variability among the domestic policy behaviour of interest groups.